Peningkatan Pemahaman Masyarakat tentang Pengurusan Tanah melalui Pelatihan dan Pendampingan Hukum di Desa Langensari Kecamatan Karang Tengah Kabupaten Cianjur Jawa Barat - Jum Anggriani; Tetti Samosir; Asep Bambang Hermanto (CV. Creative Tugu Pena, 2025)
This study aims to enhance the understanding of land administration procedures among residents of Langensari Village, Karang Tengah District, Cianjur Regency, West Java, through legal training and assistance. The main issue identified is the community's limited knowledge of land management procedures, which has led to a high percentage of uncertified land ownership (65%) and an increase in land disputes (27% over the past five years). The research employs a normative juridical method using statutory and conceptual approaches. Data were collected through both library research and fieldwork, including observations, interviews, and questionnaires. The legal training and assistance program was implemented in four stages: public outreach, technical workshops, legal consultations, and direct legal assistance. The results indicate a significant improvement in community understanding of land registration procedures (from 23% to 78%), types of land rights (from 18% to 65%), and land registration documentation (from 32% to 81%). Positive outcomes of the program include increased public interest in obtaining land certificates, a 15% reduction in land disputes, and improved access to financing for residents. The training and legal assistance model developed in this study shows strong potential for replication in other rural areas with similar characteristics. The findings underscore the need to integrate land law awareness programs into broader village development strategies and to establish an accessible, integrated land database system for the community